PENGARUH EDUKASI KESEHATAN REPRODUKSI TERHADAP PERILAKU PERSONAL HYGIENE PUTRI PADA SAAT MENSTRUASI DI SEKOLAH MENENGAH PERTAMA HKBP PARDAMEAN - Sarinulo Bago; Harsudianto Silaen (Indonesian Trust Nursing Journal, 2026)
Reproductive health is an important aspect in the lives of adolescent girls, especially during menstruation. Lack of knowledge and understanding of reproductive health can impact suboptimal personal hygiene behavior, thus increasing the risk of reproductive health disorders. The study aims to analyze the effect of reproductive health education on personal hygiene behavior of girls during menstruation at HKBP Pardamean Junior High School. This type of research is a quantitative study with a pre-experimental design with a one group pretest–posttest approach. The sampling technique is total sampling with a sample of 27 respondents. Data collection was carried out using a personal hygiene behavior questionnaire before and after the provision of reproductive health education. Data analysis was carried out univariately and bivariately using the Wilcoxon Signed Rank Test. The results of the study showed a significant influence between reproductive health education on personal hygiene behavior of girls during menstruation with a p-value <0.05. This indicates that reproductive health education can improve personal hygiene practices among adolescent girls during menstruation. It is concluded that there is a significant influence between reproductive health education and personal hygiene practices among adolescent girls during menstruation.